2018
DOI: 10.1152/japplphysiol.00118.2018
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cerebral blood flow estimated by transcranial Doppler ultrasound and single-photon emission computed tomography in elderly people with dementia

Abstract: Transcranial Doppler (TCD) ultrasonography is a non-invasive technique allowing continuous recording of cerebral blood flow (CBF) velocity. However, it is unclear whether the CBF estimated by TCD would be reliable for the comparison between individuals. The present study aimed to clarify the relationship between middle cerebral artery blood flow (MCA BF) measured by TCD and regional and total CBF measured by single photon emission computed tomography (SPECT-CBF) with a quantification software program, 3-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…reflect loss of viable tissue), or both. Lower cerebral blood flow velocity assessed at the level of large cerebral arteries with Doppler ultrasound, which may be related to lower global cerebral perfusion (45), was associated with higher risk of incident depressive symptoms in individuals with heart failure (46), and with incident depression in a large population-based study (35).In addition, cross-sectional studies in older individuals with depression have found altered global (measured at the level of large arteries) or regional (at the tissue level) cerebral perfusion, independent of cerebral atrophy (47)(48)(49). In one study, regional cerebral perfusion was altered to a greater extent in individuals with late-onset depression (defined in that study as first onset of the episode after the age of 60 years), compared to individuals with early-onset depression and individuals without any depression, and altered cerebral perfusion was associated with worse cognitive performance in these individuals (48).…”
Section: Cerebrovascular Reactivity Cerebral Autoregulation and Resting Cerebral Blood Flowmentioning
confidence: 99%
“…reflect loss of viable tissue), or both. Lower cerebral blood flow velocity assessed at the level of large cerebral arteries with Doppler ultrasound, which may be related to lower global cerebral perfusion (45), was associated with higher risk of incident depressive symptoms in individuals with heart failure (46), and with incident depression in a large population-based study (35).In addition, cross-sectional studies in older individuals with depression have found altered global (measured at the level of large arteries) or regional (at the tissue level) cerebral perfusion, independent of cerebral atrophy (47)(48)(49). In one study, regional cerebral perfusion was altered to a greater extent in individuals with late-onset depression (defined in that study as first onset of the episode after the age of 60 years), compared to individuals with early-onset depression and individuals without any depression, and altered cerebral perfusion was associated with worse cognitive performance in these individuals (48).…”
Section: Cerebrovascular Reactivity Cerebral Autoregulation and Resting Cerebral Blood Flowmentioning
confidence: 99%
“…More highly localised and direct processes could be used in future studies, if available, and these may give more definitive results. However, it is unlikely that this should be a limiting factor given that correlations between direct methods of CBF determination and TCD have been positively associated and validated (Miyazawa et al 2018 ; Willie et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because we could not measure the cerebral artery diameter, the blood flow in the middle cerebral artery was inferred from its velocity, with the assumption that the diameter was constant (1). We used this approach because V MCA measured by transcranial Doppler ultrasound had reportedly been correlated with regional cerebral blood flow measured by single-photon emission computed tomography (22).…”
Section: Measurementsmentioning
confidence: 99%